Evaluation of a Web-based education program on reducing medication dosing error: a multicenter, randomized controlled trial - Frush, Karen; Hohenhaus, Susan; Luo, Xuemei; Gerardi, Michael; Wiebe, Robert A (Pediatric emergency care, 2006)
The Broselow Pediatric Resuscitation Tape has been shown to be effective in reducing medication dosing error among pediatric emergency providers. However, the tape has often been used inappropriately or incorrectly. To evaluate whether a Web-based education program on proper use of the tape could reduce medication dosing errors and time to determine dose. A randomized, controlled trial conducted among 89 pediatric emergency providers from 3 study sites. All study subjects participated in a videotaped simulated stabilization scenario and were then randomly assigned to control or education group. After the intervention, all subjects participated in another simulation. The primary outcomes included dosing deviation from accepted dose range for each medication prescribed and dosing deviation summary, calculated by averaging dosing deviation for all medications. The secondary outcomes included time to determine a dose for each medication prescribed, and dosing time summary; that is, the average time to determine doses for all medications prescribed. No significant difference was observed in the demographic characteristics of the 2 groups. After the educational intervention, the average (12.6% vs. 24.9%) and median (7.1% vs. 20.1%) dosing deviation summary were much lower in the education group than in the control group. The difference in the median dosing deviation summary between the 2 groups was statistically significant (P = 0.0002). Similar results were observed for the dosing time. The education group demonstrated a lower average (16 vs. 20 seconds) and lower median (15 vs. 18 seconds) dosing time summary than the control group. The difference in the median dosing time summary between the 2 groups was statistically significant (P = 0.02). Analysis of each medication prescribed indicated that the decrease in the dosing deviation and dosing time in the education group was most obvious for several specific medications. The Web-based education program on the proper use of the Broselow Pediatric Resuscitation Tape could improve dosing accuracy and reduce dosing time.